A systematic review of exposure to toxic elements and neurocognitive development in children - Tingyi Guo; Moslem Lari Najafi; Junmei Zhang (Ecotoxicology and Environmental Safety)
Exposure to potentially toxic elements (PTEs) has been implicated in neurodevelopmental disorders and cognitive deficits in children. However, the extent of this association and the underlying mechanisms remain poorly understood. The objective of this systematic review is to consolidate the current body of research concerning the connection between exposure to PTEs and the neurocognitive development of children. Adhering strictly to the MOOSE guidelines, the methodological framework of this review was meticulously structured. A comprehensive and thorough search strategy was implemented across Web of Science and PubMed, with a specific focus on articles published in English up to April 15, 2024. The assessment of the identified studies was systematically carried out using the evaluation method described by Gascon et al. in 2016. Fifteen studies meeting the inclusion criteria were ultimately incorporated into the review. These studies collectively involved 8391 participants and utilized various methodologies to assess exposure to PTEs and neurodevelopmental outcomes in children. Findings from the reviewed studies suggest that exposure to PTEs such as lead, arsenic, mercury, and fluoride may be associated with adverse effects on neurocognitive development, including deficits in IQ, attention, memory, and behavioral problems. Despite the limitations of the existing literature, including study design constraints and geographic disparities, the findings highlight the need for continued research to better understand the impact of PTEs on neurocognitive development in children. Future research should employ longitudinal designs, utilize alternative biomarkers for exposure assessment, consider exposure pathways and sources, investigate cumulative effects of multiple PTEs, and ensure broader geographical representation.